Cascade Reactions to Substituted 1H-Pyrrole-3-carbonitriles via Ligand-Free Palladium(II)-Catalyzed C(sp)–C(sp2) Coupling - Wang, Zijuan; Chen, Wenteng; Luo, Haofan; He, Chang; Zhang, Guolin; Yu, Yongping (Synthesis, 2020)
An efficient and simple synthesis of substituted 1H-pyrrole-3-carbonitriles was developed. This reaction is a palladium(II)-catalyzed cascade of C(sp)–C(sp2) coupling followed by intramolecular C–N bond formation. The method can tolerate various substrates with satisfactory yields. Its ligand-free conditions and high efficiency make this method particularly attractive.
Keywords: C–C coupling; palladium; ligand-free; cascade reactions; substituted 1H-pyrrole-3-carbonitriles